ASSESSMENT OF KNOWLEDGE ABOUT PERIODONTAL DISEASE AMONG A GROUP OF HEALTH CARE PROFESSIONALS IN CHENNAI CITY: A QUESTIONNAIRE STUDY - E, SUSMITHA; ARJUNKUMAR, RADHIKA (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Objective: The main objective of this study is to assess the awareness about oral hygiene, etiology periodontal disease and awareness of treatment techniques for the same among medical professionals in Chennai city. METHODS: A survey will be carried out among a group of medical professionals comprising of interns, post graduates (PG) and faculty in medical colleges by means of questions to identify the knowledge of periodontitis, risk associated with periodontal disease and the general awareness among medical professionals with regards to periodontal care. The data obtained from the questionnaire was statistically analyzed and the results were computed. RESULTS: The results of this study show that there in increase in the knowledge about periodontal disease in postgraduates and faculty compared to interns. It was observed that the awareness increased with the number of years of experience, however, across groups there was a deficiency in the knowledge with respect to latest treatment modalities available for periodontal disease. CONCLUSION: The input from the survey can be used to organize periodontal health programs and awareness among professionals about periodontal disease and importance of treating the same. Keywords: Knowledge, Periodontal disease, Medical professionals.